PENGARUH PERMAINAN TAKE SHAPE TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI ANAK USIA 4-5 TAHUN - Rika Okmalinta; Zulkifli N; Yeni Solfiah (UIR PRESS, 2019)
Take shape games can help children to hone the ability to recognize geometry shapes. The results of field observations on the ability to recognize geometric shapes of students have not yet developed optimally. So, it is necessary to apply the game to take shape. The purpose of this study was to examine the effect of taking on the ability to recognize geometric shapes of children aged 4-5 years. This research was conducted at Dharma Wanita Persatuan Cerenti Kindergarten District Kuantan Singingi. This study used an experimental method with the design of one group pre-test post-test design with 15 samples. The data collection technique used was an observation sheet to record the activities that occurred during the given treatment. The data analysis technique used a t-test using the SPSS version 23 program. From the results of data analysis, the t-count was 14.402, greater than t-table = 2.145 with sig 0.000 <0.05 There is a significant difference in the ability to recognize geometric shapes before and after the application of the take shape game. There is an influence of the shape of the game on the ability to recognize the geometry of children aged 4-5 years in the Dharma Wanita Persatuan Cerenti Kindergarten Cerenti District Kuantan Singingi by 60.65%.